SEXISM IN EFL TEXTBOOKS USED IN INDONESIAN SCHOOLS - Syarifuddin Syarifuddin (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
Since English is a compulsory subject in Indonesian schools where students have to use certain EFL textbooks, examining sexism in these textbooks is important. This study examined sexism in three of the most widely used EFL textbooks in Indonesian schools. Six criteria of sexism were used in analysing the data, namely: generic he; generic man; titles, labels and names; occupational roles both in texts and pictures/ illustrations; omission, the number of females and males both in texts and pictures/ illustrations; and firstness, the order of mention. The analysis was based on the National Council of Teachers of English (NCTE)’s ‘Guidelines for gender-fair use of Language’ (2002) and Porecca’s study (1984). In all criteria of sexism, there is evidence that sexism is present in the EFL textbooks used in Indonesian schools. The most unbalanced and the worst finding is the firstness (the order of mentions) with the ratio 10:1 in favour of male gendered words that appear first. This study suggests that there should be improvement in the production of the EFL textbooks used in Indonesian schools.